Naturally Occurring Nanoparticles from Arthrobotrys oligospora as a Potential Immunostimulatory and Antitumor Agent. (4th December 2012) - Wang, Yongzhong; Sun, Leming; Yi, Sijia; Huang, Yujian; Lenaghan, Scott C.; Zhang, Mingjun
Abstract Arthrobotrys oligospora, a representative flesh eater in the fungal kingdom, is a potential source for natural‐based biomaterials due to the presence of specialized 3D adhesive traps that can capture, penetrate, and digest free‐living nematodes in diverse environments. The purpose of this study is to discover novel nanoparticles that occur naturally in A. oligospora and to exploit its potential biomedical applications. A new culture method, fungal sitting drop culture method, is established in order to monitor the growth of A. oligospora in situ, and observe the nanoparticle production without interfering or contamination from the solid media. Abundant spherical nanoparticles secreted from the fungus are first revealed by scanning electron microscopy and atomic force microscopy. They have an average size of 360–370 nm, with a zeta potential of –33 mV at pH 6.0. Further analyses reveal that there is ≈28 μg of glycosaminoglycan and ≈550 μg of protein per mg of nanoparticles. Interestingly, the nanoparticles significantly induce TNF‐α secretion in RAW264.7mouse macrophages, indicating a potential immunostimulatory effect. The nanoparticles themselves are also found slightly cytotoxic to mouse melanoma B16BL6 and human lung cancer A549 cells, and show a synergistic cytotoxic effect upon conjugation with doxorubicin against both cells. This study proposes a new approach for producing novel organic nanoparticles secreted from microorganisms under controlled conditions. The findings here also highlight the potential roles of the naturally occurring nanoparticles from A. oligospora as an immunostimulatory and antitumor agent for cancer immunochemotherapy.